Granular indigenous microalgal-bacterial consortium for wastewater treatment: Establishment strategy, functional microorganism, nutrient removal, and influencing factor. (June 2022) - Chen, Zhipeng; Xie, Yue; Qiu, Shuang; Li, Mengting; Yuan, Wenqi; Ge, Shijian
Graphical abstract: Highlights: IMBC presents superior wastewater adaptation and nutrient removal capacities. G-IMBC exhibits excellent settleability and efficient separation from wastewater. Initial IMBC enrichment and subsequent acclimation strategies were summarized. Interspecies interactions and microbial metabolisms were systematically introduced. Knowledge gaps, research needs, and future directions were discussed. Abstract: Granular indigenous microalgal-bacterial consortium (G-IMBC) system integrates the advantages of the MBC and granular activated sludge technologies, also with superior microalgal wastewater adaptation capacity. In this review, the concept of IMBC was firstly described, followed by its establishment and acclimation strategies. Characteristics and advantages of G-IMBC system compared to other IMBC systems (i.e., attached and floc IMBC systems) were then introduced. Moreover, the involved functional microorganisms and their interactions, as well as nutrient removal mechanisms were systematically and critically reviewed. Finally, the influencing factors including wastewater characteristics and operation factors were discussed. This study aims to provide a comprehensive up-to-date summary of the G-IMBC system for sustainable wastewater treatment.